1996
DOI: 10.1103/physrevb.53.8553
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation of vortices inside open and blind microholes

Abstract: The critical field of a thin superconducting film with a blind circular hole is found theoretically. It is shown that the value of the critical field is sensitive to the bottom thickness, but the orbital momentum, i.e., the number of vortices which nucleate inside the hole, is not sensitive. A simple boundary condition for a steplike thin film is derived and used for comparative numerical analysis of the superconductivity nucleation in a microdisk and near the hole. By increasing the thickness of the bottom of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
90
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(101 citation statements)
references
References 7 publications
10
90
0
1
Order By: Relevance
“…The only important implication for the present study is that the effect of vortex confinement in single crystal disks is the same as that of confinement in individual thin-film disks, even though in the former case only a small fraction of the total vortex length is subject to the additional interaction with the surface. Moreover, the response is independent of the disk's height, in agreement with theoretical predictions [12].…”
supporting
confidence: 76%
“…The only important implication for the present study is that the effect of vortex confinement in single crystal disks is the same as that of confinement in individual thin-film disks, even though in the former case only a small fraction of the total vortex length is subject to the additional interaction with the surface. Moreover, the response is independent of the disk's height, in agreement with theoretical predictions [12].…”
supporting
confidence: 76%
“…We have used the Bitter decoration technique to visualize the vortex configuration in the T 3 lattice for f = 1/3 and f = 1/2. As shown recently [11] the decoration contrast can be significantly improved, in the case of superconducting arrays, by using the so-called flux compression method in which a thin superconducting bottom layer converts the network coreless vortices into well-defined Abrikosov vortices. Fig.2 compares the observed vortex patterns for f = 1/3 and f = 1/2.…”
Section: Resultsmentioning
confidence: 99%
“…Superconducting films with a lattice of artificial pinning centers (APCs) have been investigated for several years 1,2,3,4,5 . It is found that the vortex lattice is highly ordered at certain matching fields, H n , where the number of flux lines equals an integer multiple n of the number of APCs.…”
mentioning
confidence: 99%